The Relationship between Atherosclerosis and Non-Alcoholic Fatty Liver Disease According to Polysystemic Ultrasound of the Arteries and Hepatic Steatometry - O. B. Dynnyk; S. E. Mostovy; G. L. Boyko; E. A. Nastenko; N. G. Gnoeva (Ukrainian Journal of Cardiovascular Surgery, 2020)
Introduction. Coronary heart disease (CHD) remains the most common cause of death and disability in Ukraine and around the world. CHD is caused by atherosclerosis. Non-alcoholic fatty liver disease (NAFLD) is considered an independent predictor of CHD.Aim. To identify the relationship between atherosclerosis and NAFLD according to polysystemic ultrasound (ps-US) of the arteries and liver steatometry.Materials and methods. We conducted an open prospective study in 2019 of 93 people, including 58 women and 35 men aged 22 to 79 years. Chronic CHD was detected in 36 patients and 57 apparently healthy individuals. US was performed by Soneus P7 (Ultrasign, Ukraine). We determined condition of the abdominal organs in the B-mode as well as the amount extent of hepatic steatosis – through steatometry by attenuation coefficient (AC) measurement – ACM) for the diagnosis of NAFLD. Atherosclerosis of the abdominal aorta and common carotid arteries (atherosclerotic plaques and the thickness of the intima-media complex) was detected.Results and discussion. There was an increase in AC (a sign of NAFLD) in 36 patients with CHD. The presence of carotid atherosclerosis confirms a higher percentage of patients with signs of hepatosis in the CHD group.Conclusions. An innovative method of quantitative ultrasound of hepatosteatosis (steatometry) can be used as a screening for the detection of NAFLD in population studies. The relationship between markers of atherosclerosis and NAFLD has been revealed according to the data of ps-US of the arteries and hepatic steatometry which allows to prescribe comprehensive treatment and evaluate its effectiveness. NAFLD can be a predictor of atherosclerosis and the formation of CHD, which gives grounds for the primary prevention of the latter.